2016
DOI: 10.1016/j.lfs.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Decreased reactive oxygen species production and NOX1, NOX2, NOX4 expressions contribute to hyporeactivity to phenylephrine in aortas of pregnant SHR

Abstract: Taken together, these results suggest that ROS production was decreased in the aortas of pregnant SHR and could contribute to higher NO bioavailability and hyporeactivity to PE in the aortas of pregnant SHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…We observed greater amount of NO in the aorta and mesenteric bed at the end of pregnancy, as indirectly measured by nitrite levels ( Figures 1A , B ). This increase in NO may be associated with increased total eNOS and p-eNOS Ser1177 expression in the aorta and higher NO concentration in aortic endothelial cells from P Wistar rats and P SHR, as already observed by our research team ( Zancheta et al, 2015 ; Troiano et al, 2016 ). Moreover, in the aorta, where NO is the main regulatory factor of vascular homeostasis, variation of NO levels is greater in NP SHR and P SHR than in NP Wistar rats and P Wistar rats, emphasizing the importance of this molecule for regulation of vascular mechanisms during pregnancy of hypertensive rats.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We observed greater amount of NO in the aorta and mesenteric bed at the end of pregnancy, as indirectly measured by nitrite levels ( Figures 1A , B ). This increase in NO may be associated with increased total eNOS and p-eNOS Ser1177 expression in the aorta and higher NO concentration in aortic endothelial cells from P Wistar rats and P SHR, as already observed by our research team ( Zancheta et al, 2015 ; Troiano et al, 2016 ). Moreover, in the aorta, where NO is the main regulatory factor of vascular homeostasis, variation of NO levels is greater in NP SHR and P SHR than in NP Wistar rats and P Wistar rats, emphasizing the importance of this molecule for regulation of vascular mechanisms during pregnancy of hypertensive rats.…”
Section: Discussionsupporting
confidence: 81%
“…Pregnancy in normotensive Wistar rats and spontaneously hypertensive rats (SHR) is a physiological process characterized by significant reduction in mean arterial pressure despite increased plasma volume. This phenomenon stems from reduced peripheral vascular resistance associated with decreased pressor responses and reduced contractile response to vasoconstrictors ( Barron et al, 1984 ; Chu and Beilin, 1993a , b ; Ballejo et al, 2002 ; Elias et al, 2008 ; Stennett et al, 2009 ; Ognibene et al, 2012 ; Zancheta et al, 2015 ; Troiano et al, 2016 ). Compared to blood vessels from non-pregnant rats, eNOS activity is increased in systemic arteries from late pregnant normotensive and hypertensive rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10A. In endothelial cells of normotensive and hypertensive male rats [32] and in pregnant and non-pregnant normotensive and hypertensive rats [38] were observed that apocynin stimulated an increase in NO concentration and decreased ROS levels. Moreover, we also observed that apocynin increased Ca +2 concentration ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Using a flow cytometer (Attune™ Acoustic Focusing Cytometer, Applied Biosystems, Vic, Australia), samples were excited with a blue laser at 488 nm and emission at 530/30 nm, to DAF-2/DA and FLUO-3AM experiments, and with a blue laser at 488 nm and emission at 585/ 42 nm, to DHE experiments. A software (Attune Cytometric Software, Applied Biosystem) analyzed the cytofluorographic tracings generated and the results were expressed as the mean values of the medians of fluorescence intensity (FI) from the cells stimulated with fluorescent probes in presence or absence of apocynin or diapocynin stimuli, according to Potje et al [37] and Troiano et al [38]. The obtained values were analyzed and compared between cells incubated with apocynin or diapocynin.…”
Section: Flow Cytometry Experiments: Aortic Endothelial Cellsmentioning
confidence: 99%